2016
DOI: 10.1007/s40120-016-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Current Data on and Clinical Insights into the Treatment of First Episode Nonaffective Psychosis: A Comprehensive Review

Abstract: Implementing the most suitable treatment strategies and making appropriate clinical decisions about individuals with a first episode of psychosis (FEP) is a complex and crucial task, with relevant impact in illness outcome. Treatment approaches in the early stages should go beyond choosing the right antipsychotic drug and should also address tractable factors influencing the risk of relapse. Effectiveness and likely metabolic and endocrine disturbances differ among second-generation antipsychotics (SGAs) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 188 publications
(218 reference statements)
1
8
0
Order By: Relevance
“…Early detection and interventions have been strongly proposed because the first 5 years after onset is considered the critical period when the biological and psychological changes are most extensive, and the brain shows the maximum plasticity (McGorry, Killackey, & Yung, 2008). Recent‐onset psychosis is defined as the first 5 years after diagnosis (Crespo‐Facorro, Pelayo‐Teran, & Mayoral‐van Son, 2016) which is the period of high risk for relapse and suicide, and the critical time to build stable social identity and relationships (McGorry et al, 2008). There is evidence that early intervention during this period is most effective, resulting in fewer symptoms, better outcomes and good recovery (Bird et al, 2010; Iyer et al, 2015; Skalli & Nicole, 2011; Srihari, Shah, & Keshavan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Early detection and interventions have been strongly proposed because the first 5 years after onset is considered the critical period when the biological and psychological changes are most extensive, and the brain shows the maximum plasticity (McGorry, Killackey, & Yung, 2008). Recent‐onset psychosis is defined as the first 5 years after diagnosis (Crespo‐Facorro, Pelayo‐Teran, & Mayoral‐van Son, 2016) which is the period of high risk for relapse and suicide, and the critical time to build stable social identity and relationships (McGorry et al, 2008). There is evidence that early intervention during this period is most effective, resulting in fewer symptoms, better outcomes and good recovery (Bird et al, 2010; Iyer et al, 2015; Skalli & Nicole, 2011; Srihari, Shah, & Keshavan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that baseline clinical characteristics could be useful in the field of personalized medicine to predict the response phenotype from these four and to apply individualized treatment. Our results are especially relevant if we take into account that they were obtained with FEP patients and FEP recovery has come into focus as the main goal of any treatment strategy .…”
Section: Discussionmentioning
confidence: 94%
“…The first line of management is low-dose antipsychotics; treatment with atypical antipsychotics in low doses have exhibited high remission rates. [23] Here, it must be stressed that medication adherence is one of the most important factors independently affecting the remission in FEP. [4] Medication adherence improves the outcome through reducing the risk of relapse and fewer hospitalizations.…”
Section: Introductionmentioning
confidence: 99%